2016
DOI: 10.1186/s12974-016-0647-y
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to the RNA-binding protein hnRNP A1 contribute to neurodegeneration in a model of central nervous system autoimmune inflammatory disease

Abstract: BackgroundNeurodegeneration is believed to be the primary cause of permanent, long-term disability in patients with multiple sclerosis. The cause of neurodegeneration in multiple sclerosis appears to be multifactorial. One mechanism that has been implicated in the pathogenesis of neurodegeneration in multiple sclerosis is the targeting of neuronal and axonal antigens by autoantibodies. Multiple sclerosis patients develop antibodies to the RNA-binding protein, heterogeneous nuclear ribonucleoprotein A1 (hnRNP A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 68 publications
2
28
0
Order By: Relevance
“…Several mechanisms of neurodegeneration have been observed in MS, including axonal transport deficits, mitochondrial dysfunction, and the humoral immune response (Benarroch, 2015;Campbell et al, 2011;Coleman, 2005;De Vos, Grierson, Ackerley, & Miller, 2008;Dutta et al, 2006;Huizinga, Gerritsen, Heijmans, & Amor, 2008;Mathey et al, 2007;Nikic et al, 2011). Additionally, autoantibodies to heterogeneous nuclear ribonucleoprotein A1 (hnRNP A1), an RNA-binding protein (RBP), have been identified in MS patients and are implicated in neuronal dysfunction and damage (Douglas et al, 2016;Lee et al, 2011;Levin et al, 2002). Additionally, autoantibodies to heterogeneous nuclear ribonucleoprotein A1 (hnRNP A1), an RNA-binding protein (RBP), have been identified in MS patients and are implicated in neuronal dysfunction and damage (Douglas et al, 2016;Lee et al, 2011;Levin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several mechanisms of neurodegeneration have been observed in MS, including axonal transport deficits, mitochondrial dysfunction, and the humoral immune response (Benarroch, 2015;Campbell et al, 2011;Coleman, 2005;De Vos, Grierson, Ackerley, & Miller, 2008;Dutta et al, 2006;Huizinga, Gerritsen, Heijmans, & Amor, 2008;Mathey et al, 2007;Nikic et al, 2011). Additionally, autoantibodies to heterogeneous nuclear ribonucleoprotein A1 (hnRNP A1), an RNA-binding protein (RBP), have been identified in MS patients and are implicated in neuronal dysfunction and damage (Douglas et al, 2016;Lee et al, 2011;Levin et al, 2002). Additionally, autoantibodies to heterogeneous nuclear ribonucleoprotein A1 (hnRNP A1), an RNA-binding protein (RBP), have been identified in MS patients and are implicated in neuronal dysfunction and damage (Douglas et al, 2016;Lee et al, 2011;Levin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, administration of antibodies to non-myelin antigens, such as neurofascin and neurofilament, in experimental autoimmune encephalomyelitis (EAE) models leads to axonal and neuronal injury (Huizinga et al, 2008;Mathey et al, 2007). Additionally, autoantibodies to heterogeneous nuclear ribonucleoprotein A1 (hnRNP A1), an RNA-binding protein (RBP), have been identified in MS patients and are implicated in neuronal dysfunction and damage (Douglas et al, 2016;Lee et al, 2011;Levin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that hnRNP A1 binds to spastin, a gene responsible for hereditary spastic paraparesis, which produces a phenotype that is closely similar to MS [162]. This finding was also replicated by another group which found a hnRNP A1 antibodies in animal models also contributed to neurodegeneration as evidenced by increased localization to stress granules, worsened experimental autoimmune encephalomyelitis (EAE) cases, modifications in phenotype from flaccid to spastic paralysis, and selective degeneration in the cerebellar white matter [166].…”
Section: Multiple Sclerosismentioning
confidence: 84%
“…Levin et al (20) revealed that autoantibodies to hnRNPA1 may cause neurodegenerative changes. Animal experiments have demonstrated that hnRNPA1 antibodies are associated with multiple sclerosis (21). Sueoka et al (22) detected antibodies in the cerebrospinal fluid of 35 patients with multiple sclerosis and reported that 32 of them had antibodies against the hnRNPB1 protein.…”
Section: Discussionmentioning
confidence: 99%